Autism Spectrum Disorder Recent Advances - Fitzgerald, Michael (IntechOpen, 2015)
This book starts with a new sub category of Autism Criminal Autistic Psychopathy and school shootings. It focuses on a number of interventions, including speech and language pathology, speech and language assessment instruments, occupational therapy, improving functional language development in autism with natural gestures, communication boards etc as well as helping people with autism using the pictorial support, training of concepts of significant others, theory of mind, social concepts and a conceptual model for empowering families of children with autism cross culturally. It also examines the issue of hyperandrogenism and evidence-based treatments of autism. In terms of assessment, it focuses on psychological and biological assessment including neurotransmitters systems, structural and functional brain imaging, coping strategies of parents, examines the intertwining of language impairment, specific language impairment and ASD, as well as implicit and spontaneous Theory of Mind reading in ASD. In terms of aetiology, it focuses on genetic factors, epigenetics, synaptic vesicles, toxicity during neurodevelopment, immune system and sex differences. It also examines the link between social cognitive anatomical and neurophysiologic biomarkers and candidate genes. This book will be relevant to all mental health professionals because autism occurs in all the different areas of psychiatry and professionals who will find it helpful will be psychiatrists, psychologists, social workers, nurses, teachers and all those working with persons with Autism including parents who nowadays are interested in knowing more and more, at a detailed level about their children or adults with autism.